2011
DOI: 10.1007/s13197-011-0481-2
|View full text |Cite
|
Sign up to set email alerts
|

Determination and characterization of kernel biochemical composition and functional compounds of Persian walnut oil

Abstract: Kernel chemical composition and fatty acids profile of three walnut cultivars (Toyserkan, Chaboksar and Karaj) was analyzed. Some physicochemical properties, total phenolics content (TPC), ortho-diphenols content (ODC) and total tocopherol concentration (TTC) of extracted oils from the walnuts were also determined. The antioxidant activity of oil was measured by 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging capacity and β-carotene bleaching assays. The analysis of chemical composition revealed that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 25 publications
7
72
1
1
Order By: Relevance
“…The highest essential oil content increases the product fragrance, quality, and shelf life. We agree with Gharibzahedi et al (2014) that the oil stability can be indicated to high antioxidant activity due to the phenol content in oil. The 10,000 cc OTR film at 8°C and 30,000 cc OTR film at 24°C treatments retained more essential oil compared to the other treatments (Table 3).…”
Section: Leaf Quality Parameterssupporting
confidence: 90%
“…The highest essential oil content increases the product fragrance, quality, and shelf life. We agree with Gharibzahedi et al (2014) that the oil stability can be indicated to high antioxidant activity due to the phenol content in oil. The 10,000 cc OTR film at 8°C and 30,000 cc OTR film at 24°C treatments retained more essential oil compared to the other treatments (Table 3).…”
Section: Leaf Quality Parameterssupporting
confidence: 90%
“…Previously, Simsek (2010) reported average protein, oil and ash content between 13.70-20.18%, 58.88-65.64% and 1.88-2.89% among walnut selections. Kahraman (2006) Gharibzahedi et al (2014) reported protein, total oil, carbohydrate, ash and fiber content of 3 walnut cultivars from Iran that ranged from 13.77 to 14.92%, 62.3-67.3%, 12.84 to 16.67%, 2.09 to 2.24% and 4.2 to 4.6%, respectively. The current results are comparable with the above reported studies.…”
Section: Physico-chemical Characteristicsmentioning
confidence: 99%
“…Walnuts oil is major product of walnut production and is one of the important special oils used for salad dressing and cooking (Oliveira et al 2002). Besides walnut oil and protein, Walnut contain 12~16% carbohydrates, 1.5~2.0% cellulose, 1.7~2.0% mineral (Lavedrine et al 2000;Prasad 2003;Savage 2001;Sze-Tao and Sathe 2000b;Wardlaw 1999;Gharibzahedi et al 2011). As a by-product of oil production, walnut protein products are therefore being considered as an additional source of plant protein for use in human food products.…”
Section: Introductionmentioning
confidence: 99%